2017
DOI: 10.21037/acs.2017.09.02
|View full text |Cite
|
Sign up to set email alerts
|

Review of minimal access versus transcatheter aortic valve replacement for patients with severe aortic stenosis

Abstract: Transcatheter aortic valve replacement (TAVR) and minimally invasive aortic valve replacement (miniAVR) have become alternatives to surgical aortic valve replacement via median sternotomy (SAVR) to treat severe aortic stenosis (AS). Despite increased interest and utilization, few studies have directly compared TAVR and miniAVR. A review of the current literature shows TAVR to be an indispensable tool for inoperable, high-risk, and perhaps intermediate-risk patients with severe AS. However, it is associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…It is associated with longer aortic crossclamp and cardiopulmonary bypass (CPB) times; however, the use of rapid deployment valves can circumvent this. Studies comparing TAVI and miniAVR demonstrate decreased postoperative mortality, valvular regurgitation, and incidence of stroke in the miniAVR cohorts [51].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is associated with longer aortic crossclamp and cardiopulmonary bypass (CPB) times; however, the use of rapid deployment valves can circumvent this. Studies comparing TAVI and miniAVR demonstrate decreased postoperative mortality, valvular regurgitation, and incidence of stroke in the miniAVR cohorts [51].…”
Section: Discussionmentioning
confidence: 94%
“…Meanwhile, the surgical approach has improved and evolved to a reduction in surgical aggression. TAVI and minimally invasive aortic valve replacement [51] have become alternatives to surgical aortic valve replacement via median sternotomy (SAVR) to treat severe aortic stenosis (AS). Despite increased interest and utilization, few studies have directly compared TAVI and miniAVR.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Terwelp et al showed TAVR was associated with an increased risk of stroke but a reduced rate of atrial fibrillation compared to mini‐AVR. However, it is important to note that the patients undergoing TAVR tend to be at high‐risk, while patients assigned to mini‐AVR have been low‐risk . Therefore, it is difficult to draw meaningful conclusions even with propensity‐matched studies.…”
Section: Discussionmentioning
confidence: 99%
“…For the therapeutic choice between TAVI, mini-AVR and CAVR, a dedicated heart team assesses each patient based on previous cardiologic history and baseline characteristics, calculate the risk of surgery, evaluate the feasibility of TAVI or surgery, and local experience. TAVI is associated with increased pacemaker implantation, vascular complications and paravalvular leakage [31]. For mini-AVR and CAVR these complications are less common.…”
Section: Discussionmentioning
confidence: 99%